Management of oral manifestation of toxic epidermal necrolysis due to antituberculosis drugs - Dwi Handayani; Anandina Irmagita Soegyanto; Indriasti Indah Wardhany (Faculty of Dentistry, Universitas Gadjah Mada, 2026)
Toxic epidermal necrolysis (TEN) is severe and potentially fatal hypersensitivity reactions, frequently triggered by drugs, characterized by extensive epidermal detachment on mucocutaneous. Drugs that have adverse effects on TEN are antibiotics, anticonvulsants, antiviral, antitubercular, uric acid lowering and nonsteroidal anti-inflammatory drugs (NSAID). This case report discusses the management of TEN oral manifestations caused by anti-tuberculosis drugs (ATD). A 56-year-old male inpatient at Universitas Indonesia Hospital (RSUI) was referred to Oral Medicine Unit due to dry and bleeding lips. He was diagnosed with TEN due to ATD. Extra oral examination showed brown crust on upper and lower circumoral area and blackish red crusts on the upper and lower lips with minor bleeding. Intra oral examination revealed multiple erosions, ulcers, and poor oral hygiene. The established working diagnosis was oral manifestation of TEN, which was managed with NaCl 0.9% solution, clobetasol propionate 0.05% and Vaseline® album concoction, antibiotic cream, chlorhexidine gluconate 0.2% mouthwash, and educating the patient to maintain oral hygiene. The therapy improved the patient’s condition. In the comprehensive management of TEN, dentists play an important role in treating oral manifestations and improving patient’s oral health through adequate food intake and nutritional balance for better quality of life and prognosis.